1997
DOI: 10.1063/1.120143
|View full text |Cite
|
Sign up to set email alerts
|

Strong blue and violet photoluminescence and electroluminescence from germanium-implanted and silicon-implanted silicon-dioxide layers

Abstract: The photoluminescence (PL) and electroluminescence (EL) properties of Ge-implanted SiO2 layers thermally grown on a Si substrate were investigated and compared to those of Si-implanted SiO2 films. The PL spectra from Ge-implanted SiO2 were recorded as a function of annealing temperature. It was found that the blue-violet PL from Ge-rich oxide layers reaches a maximum after annealing at 500 °C for 30 min, and is substantially more intense than the PL emission from Si-implanted oxides. The neutral oxygen vacancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
100
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(116 citation statements)
references
References 17 publications
13
100
0
3
Order By: Relevance
“…On the contrary, the Ge-implanted sample showed CL peak at 3.12 eV (397 nm in wavelength) in UV-blue region at room temperature. This CL peak is well agreed with the CL spectra reported by Rebohle et al [1,13] and H.-J. Fitting et al [11].…”
Section: Raman Spectroscopy For Ge-ge Bondingsupporting
confidence: 81%
See 1 more Smart Citation
“…On the contrary, the Ge-implanted sample showed CL peak at 3.12 eV (397 nm in wavelength) in UV-blue region at room temperature. This CL peak is well agreed with the CL spectra reported by Rebohle et al [1,13] and H.-J. Fitting et al [11].…”
Section: Raman Spectroscopy For Ge-ge Bondingsupporting
confidence: 81%
“…Although 500-nm-thick SiO 2 film including Ge NPs was reported to show blue and violet electroluminescence by applying a voltage of 350 V [1], the decrease of the operation voltage is demanded for application to light emission source for communication in a LSI chip and other versatile applications [2]. Ge nanoparticles should be formed in a considerably thin SiO 2 layer to fulfill this requirement.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, violet-blue and blue PL emission have been reported from Ge implanted SiO 2 layers and there exist controversy regarding the origin of the violetblue PL emission. 4 5 Rebohle et al 6 reported a strong blueviolet PL and electroluminescence from Ge-implanted and Si-implanted SiO 2 layer and they attributed the observed PL to neutral oxygen vacancies in SiO 2 . Similarly, Sahoo * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Это обусловлено наблюдением целого ряда эффектов, которые открывают новые перспективы для их использования. Например, в пленках SiO 2 c молекулярно-подобными нанокластерами германия возбуждается фото-и электролюминесцен-ция [1,2]. Это позволяет надеяться на их использование при создании систем с оптической связью на кремнии.…”
Section: Introductionunclassified